Report of the Sotalia guianensis Pre-Assessment Workshop: Main Results and Status of Current Knowledge - Domit, Camila; Caballero, Susana; Miranda, Adriana; Fruet, Pedro; Torres-Florez, Juan Pablo; Cunha, Haydee; Farro, Ana Paula; Azevedo, Alexandre; Bisi, Tatiana; Briceño, Yurasi; Cremer, Marta J.; Tardin, Rodrigo; et al. (International Whaling Commission, 2021)
In 2014, a Resolution was approved by the IWC for establishing new, specific Terms of Reference to consolidate the Scientific Committee’s mandate on small cetaceans within its broader working program. This program opens the possibility of periodic reviews about the current knowledge and threats, as well as the possibility to implement Conservation Plans for Endangered Species within the scope of the IWC when appropriate. The first Conservation and Management Plan for a small cetacean was proposed for the franciscana dolphin (Pontoporia blainvillei) and endorsed by the Commission in 2016. In recent years, the Scientific Committee has worked to better understand the extent of multiple disturbances on small cetaceans - habitat degradation, incidental and intentional catches (for human consumption, bait, trade and traditional use) - to mitigate these threats. This task force resulted in a series of workshops to enable local research groups to collect, share and analyse data aiming to paint a clearer broad picture of the conservation status of these species. River and estuarine dolphins in South America have been of great concern by the Small Cetacean Sub-committee (SM). During the IWC/67b Scientific Committee Meeting, held in Bled in 2018, Slovenia, the sub-committee on small cetaceans listed the Guiana dolphin (Sotalia guianensis) as a priority species for an evaluation of its conservation status in the upcoming years (2019/20 – presented at the meeting as SC/67b/SM/WP/12). The Guiana dolphin is restricted to coastal areas, including estuaries and bays in western tropical South America, from Nicaragua in Central America to Santa Catarina state in southern Brazil (Flores and Da Silva, 2009). Due to its exclusive coastal habits, the distribution of Guiana dolphins overlaps with densely human coastal populations, raising concerns on the status of various populations (Avila et al., 2018). It is important to clarify that although the taxonomy of this genus has been controversial, some of the main questions, regarding the taxonomic identification of Sotalia dolphins in the Maracaibo Lake and in the Orinoco River, have been recently confirmed to be Sotalia guianensis (Caballero et al., 2018; Caballero et al., 2010). The Guiana dolphin was previously listed by IUCN Red List as ‘Data deficient’ (DD) because the data available on abundance, trends, and mortality levels or rates were considered inadequate for assigning it to a single Red List category at the time (Secchi, 2012). However, the current assessment classified the species as ‘Near threatened’ (NT) (Secchi et al., 2018), approaching criterion A2d+3d+4d. Regional assessments classified the species in different categories depending on the country and availability of data on each population (details in the section ‘Management and Conservation actions’). In 2006, the SM reviewed the status of the Sotalia genus, as part of a review of the small cetaceans of the Caribbean and the western tropical Atlantic. Since then, not only the taxonomy of the genus has been clarified, but also new data on the dolphin populations from the Orinoco River, French Guiana and Maracaibo Lake has been collected and analysed. While bycatch in artisanal gillnets is a major threat to Guiana dolphin populations, other threats such as intentional captures for bait, habitat loss, high contaminant load, and diseases (MeCV, herpesvirus, skin diseases of unknown aetiology), are emerging factors depleting some Guiana dolphin populations. For example, recently a high mortality event in the populations of Sepetiba and Ilha Grande bays in southeastern Brazil has been associated with morbillivirus (Groch et al., 2018). Also, deliberate capture of Guiana dolphins for human consumption has been recorded in Maracaibo Lake (Yurasi Briceño, pers. comm.; Barrios-Garrido et al. (2015) where the population is exposed to pollutants, particularly from oil spills (Espinoza-Rodríguez et al., 2019). Throughout its distribution, Guiana dolphins are facing habitat degradation and loss due to anthropogenic activities, such as high boat traffic and their high noise levels, eutrophication due to run-off and pollution from agriculture, mining and industrial activities to name but a few (Barrios-Garrido et al., 2016; Crespo et al., 2010; Secchi et al., 2018). Given these threats, an assessment of population structure and viability, temporal trends in abundance and in space use, and estimative of population connectivity are urgently needed to guide discussions by the SM sub-committee, regarding the sub-committee priority agenda focusing on riverine and estuarine dolphins from South America (IWC, 2019). A pre-assessment of the status of knowledge about Sotalia guianensis was proposed, due to the difficulty in obtaining summarised data in a timely manner during IWC annual Scientific Committee meetings, since much information is scattered in grey literature in local research groups along the wide distribution range of the species. The pre-assessment plan included holding two intersessional workshops following SC68B and probably SC69A. Dr. Camila Domit volunteered to lead the organisation of these workshops in partnership with Centro Nacional de Pesquisa e Conservação de Mamíferos Aquáticos do Instituto Chico Mendes de Conservação a Biodiversidade (CMA/ICMBio), Brazil. The first Guiana Dolphin (GD) Pre-Assessment Workshop was held in the city of Lima in October 2018, during the SOLAMAC meeting. The attendance was limited and composed mainly of researchers from south/southeastern Brazil, in addition to one researcher from Colombia. They mapped resident populations of Guiana dolphins and the ongoing research efforts, as well as they listed the research teams working with the species along its distribution that would be relevant to conduct the review. The group also delineated a participative strategy to compile the knowledge about Guiana dolphins supporting a future assessment. Because the species distribution is transboundary, covering an extensive coastal area, and there are many experts focusing on this species, the group decided to develop an online questionnaire to circulate for all institutions, research teams and individuals identified. A total of 35 experts answered the questionnaire (see Annex B for their contact details), including their opinions for prioritising locations and scientific researches in supporting improvements in conservation actions. The results are summarised in the ‘Expert elicitation’ section of this report. The Second Intersessional Workshop for Pre-Assessing the Status of Knowledge of Guiana Dolphins had two goals. The first was gathering and analysing information collected by the online questionnaire; the second, was compiling the available information on a series of population, biological and ecological parameters, as well as about threats, along the species distribution. Supported by the compiled knowledge, the participants collaborated to delineate conservation measures and research needs both in national and international contexts. The second Workshop was held in Santos, São Paulo, from 26-28 November 2019, at the Instituto Chico Mendes de Conservação da Biodiversidade/Centro Nacional de Pesquisa e Conservação de Mamíferos Aquáticos (ICMBIO/CMA). The Workshop was divided into five sessions, following the priority topics listed by the IWC for the conservation of the species: (1) population structure; (2) abundance and population trends; (3) biological parameters; (4) threats and its potential effects; and (5) management and conservation. A list of experts relevant to the aims of the Workshop from each country were identified during the SC/67b and the Guiana Dolphin Workshop held in Peru during the 2018 SOLAMAC meeting, and in consultation with the Scientific Committee (SC) Vice-Chair, and co-Chairs of SM. There were 13 experts on Guiana dolphin research from three countries (Brazil, Colombia and Venezuela) and another 20 participants to the Workshop. Information gathered from the literature review, ongoing projects and the expert elicitation via online questionnaire were used by the group of Point of Contact (POCs) and other co-authors to compile and present the best up-to-date information on the species. The participants list is given as Annex A and the Agenda is given as Annex C.